Persistence of infectious SARS‐CoV‐2 particles for up to 37 days in patients with mild COVID‐19. Issue 7 (24th October 2021) - Zahn, Tobias; Mhedhbi, Ines; Hein, Sascha; Raupach, Jan; Miskey, Csaba; Husria, Younes; Bayanga, Kathrin; Bartel, Detlef; Vieths, Stefan; Ivics, Zoltan; Oberle, Doris; Keller‐Stanislawski, Brigitte; et al.
Abstract: Background: People suffering from COVID‐19 are typically considered non‐infectious 14 days after diagnosis if symptoms have disappeared for at least 48 h. We describe three patients who independently acquired their infection. These three patients experienced mild COVID‐19 and completely recovered symptomatically within 10 days, but remained PCR‐positive in deep pharyngeal samples for at least 38 days. We attempted to isolate virus from pharyngeal swabs to investigate whether these patients still carried infectious virus. Methods: Infectious virus was amplified in Vero E6 cells and characterized by electron microscopy and WGS. The immune response was investigated by ELISA and peptide arrays. Results: In all three cases, infectious and replication‐competent virus was isolated and amplified in Vero E6 cells. Virus replication was detected by RT‐PCR and immunofluorescence microscopy. Electron microscopy confirmed the formation of intact SARS‐CoV‐2 particles. For a more detailed analysis, all three isolates were characterized by whole‐genome sequencing (WGS). The sequence data revealed that the isolates belonged to the 20A or 20C clade, and two mutations in ORF8 were identified among other mutations that could be relevant for establishing a long‐term infection. Characterization of the humoral immune response in comparison to patients that had fully recovered from mild COVID‐19 revealed a lack of antibodies binding to sequential epitopes of the receptor‐binding domain (RBD) for the long‐term infected patients. Conclusion: Thus, a small portion of COVID‐19 patients displays long‐term infectivity and termination of quarantine periods after 14 days, without PCR‐based testing, should be reconsidered critically. Abstract : This study shows three long‐term SARS‐CoV‐2 PCR‐positive patients persistently producing infectious virus for up to 38 days without lasting symptoms. Patients displayed low antibody titers and decreased binding of IgG against sequential epitopes of spike protein in comparison to patients that fully recovered from mild COVID‐19. WGS revealed that isolates belong to the 20A or 20C clade and viral eradication might be affected by two mutations in ORF8.Abbreviations: COVID‐19, coronavirus disease 2019; M, membrane protein; ORF, open reading frame; qPCR, quantitative polymerase chain reactions; S, spike protein; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; WGS, whole genome sequencing